A novel mode-division (de)multiplexer with degenerate modes output for MIMO-FREE applications - Xing, Huadong; Su, Yingqun; Gao, Yan; Li, Xin; Zheng, Hongjun; Bai, Chenglin; Hu, Weisheng; Xu, Hengying (Frontiers in Physics, 2022)
In this study, we propose a novel three-dimensional architecture mode (de)multiplexer with degenerate modes output using a pure silica FMF ring core transmission channel, which solves the problem caused by random mode rotation and can be used in multiple-input multiple-output free (MIMO-FREE) applications such as data center application in the future. By using the pure silica FMF ring core transmission channel and larger effective refractive index difference, the performance with low loss, high extinction ratio (ER) and low crosstalk is achieved. The main channel with a few-mode fiber (FMF) ring-core structure supports the modes LP01, LP11, and LP21, and the large effective refractive index difference between each mode in the core ensures low crosstalk characteristics between the modes. Using the pure silica core channel can effectively reduce propagation attenuation and fusion loss. Our proposed MUX/DEMUX with degenerate modes output is achieved when the degenerate modes LP11a/LP11b and LP21a/LP21b are transmitted as two independent mode signals, which can be used in MIMO-FREE applications. The extinction ratios (ERs) of the degenerate modes LP11 and LP21 are kept above 31.66 dB and 24.43 dB, respectively, and the ER of mode LP01 is kept above 38.72 dB in the C band. The coupling efficiency of mode LP01 is approximately 0 dB, which is almost unchanged with the increase of the wavelength. The coupling efficiency of LP11 is higher than −3.49 dB and that of LP21 is higher than −7.24 dB in the whole C-band. At 1550 nm, the coupling efficiencies of modes LP01, LP11, and LP21 are −0.002 dB, −0.052 dB, and −0.178 dB, respectively. The coupling efficiency and ER of LP01 mode are the best, and those of the degenerate mode LP11 are always better than those of mode LP21. Our proposed MUX/DEMUX achieves low crosstalk and high ER performance and solves the problem caused by the degenerate modes rotations during transmission.